Understanding China's role as a development partner in Sarawak - Koh, Sylvia (2023)
China has become an important development partner in Sarawak. Yet this role has become largely technical rather than financial, as the state government has shifted to assert greater control over strategic sectors. Changes in the Sarawak government’s future development priorities may also dilute China’s prominence as a development partner.